Determinants Of Islamic Insurance Purchase Intention Among Generation Z In Surakarta: An Extended Theory Of Planned Behavior Approach - Muhammad Mario Febrian Saputra; Mufti Arief Arfiansyah (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2026)
This study examines the determinants of Generation Z’s purchase intention toward Islamic insurance in Surakarta City using an extended Theory of Planned Behavior (TPB) framework. Despite the positive growth of the Islamic insurance industry in Indonesia, the level of insurance literacy and public participation remains relatively low, particularly among young generations. This condition is further exacerbated by negative risk perceptions and declining public trust due to several insurance failure cases. Positioning itself within behavioral finance and Islamic economics literature, this study integrates Islamic insurance literacy, perceived risk, social environment, and trust as explanatory variables influencing purchase intention. Employing a quantitative explanatory research design, data were collected from 100 Generation Z respondents in Surakarta City using a structured questionnaire and analyzed through multiple linear regression with SPSS. The results indicate that Islamic insurance literacy, social environment, and trust have a positive and significant effect on purchase intention, while perceived risk has a negative and significant effect. Trust emerges as the most influential factor in shaping purchase intention. These findings highlight the importance of strengthening literacy programs, improving institutional credibility, and managing risk perceptions to enhance Generation Z’s engagement with Islamic insurance products. This study contributes empirically by offering an integrated behavioral model that explains Islamic insurance purchase intention among Generation Z in a local Indonesian context.